Extreme aircraft - Miller, Ron 1947- (Collins, 2007)
Extreme Aircraft looks at the first, the biggest, the fastest, and the strangest aircraft, as well as the men and women who built and flew them. From the prophetic flying machines of Leonardo da Vinci to the astral journeys of the space shuttle, these pages tell the story of genius inventors, bullish financiers, ace pilots, brave adventurers, and the visionary technology used in pursuing the dream of flight.